1982
DOI: 10.1679/aohc.45.1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural basis of intestinal absorption.

Abstract: Summary. The mechanisms of intestinal absorption were reviewed and discussed from the viewpoint of fine morphology of the small-intestinal epithelium. After reviewing the fine structural specializations of intestinal absorptive cells, particular emphasis was given to the morphological aspects of the first entry of gut contents into the intestinal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Among these, the mucosa plays essential roles in digestion and absorption, whereas the submucosa acts as the skeleton of the intestine to integrate the internal mucosa and the external muscle layers. A considerable number of studies have dealt with questions in intestinal morphology (for review; TRIER and RUBIN, 1965;KULENKAMPFF, 1975;YAMAMOTO, 1982;MADARA and TRIER, 1987). However, most of the previous efforts, have focused on the epithelial cells from rather limit-ed view points, and the overall structure of the intestinal mucosa has been far from fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the mucosa plays essential roles in digestion and absorption, whereas the submucosa acts as the skeleton of the intestine to integrate the internal mucosa and the external muscle layers. A considerable number of studies have dealt with questions in intestinal morphology (for review; TRIER and RUBIN, 1965;KULENKAMPFF, 1975;YAMAMOTO, 1982;MADARA and TRIER, 1987). However, most of the previous efforts, have focused on the epithelial cells from rather limit-ed view points, and the overall structure of the intestinal mucosa has been far from fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Pinocytotic absorption diminished absorption and intracellular digestion of proteins lends a possible adaptive advantage. This mechanism of digestion may compensate for incomplete digestion by allowing for the assimilation of macromolecular proteins and is apparent in the undeveloped alimentary canals of some other chordates, including some fetal and infant mammals (see reviews in Yamamoto 1982, Gauthier & Landis 1972 as well as in larvae and adult stomachless fishes (Yamamoto 1966, Kapoor et al 1975, Noaillac-Depeyre & Gas 1976, Weinberg 1976, Stroband 1977, Stroband & Van Der Veen 1981.…”
Section: Digestive Mechanismsmentioning
confidence: 99%
“…These villi are covered with epithelial tissue, which absorbs nutrients and provides a barrier against harmful substances. Transmission electron microscopy (TEM) has shown that the intestinal epithelium consists of a single layer of columnar epithelial cells on top of a continuous sheet of basal lamina (16). Because epithelial cells are sealed by the zonula occludens on the apical side, large nutrients, including carbohydrates and proteins, are absorbed from the intestinal lumen into the epithelial cells after digestion to smaller molecules (e.g., monosaccharides and amino acids); these smaller molecules are then released from the basolateral side of the cells, followed by accumulation in the blood capillary network beneath the epithelium (12).…”
mentioning
confidence: 99%